2010
DOI: 10.3174/ajnr.a2255
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Morphology and Signal Intensity of Alar Ligaments in Healthy Volunteers Using MR Imaging

Abstract: BACKGROUND AND PURPOSE:Evaluation of alar traumatic injuries by using MR imaging is frequently performed. This study investigates the variability of morphology and signal intensity of alar ligaments in healthy volunteers so that pathology can be more accurately defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 31 publications
2
16
0
5
Order By: Relevance
“…However, alar and transverse ligament high signal intensity is reported to be frequent also in healthy noninjured persons without neck pain. 4,5,7,8 The high signal intensity is unlikely to be caused by pain-induced neck immobility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, alar and transverse ligament high signal intensity is reported to be frequent also in healthy noninjured persons without neck pain. 4,5,7,8 The high signal intensity is unlikely to be caused by pain-induced neck immobility.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in patients with chronic WAD 6,9,10 but also in noninjured controls. 4,5,7,8 In the only study of alar and transverse ligament high signal intensity in acute WAD, such high signal intensity was not related to crash factors, was not more frequent when compared with noninjured controls without neck pain, and did not influence clinical outcome after 12 months. 8,11 Traumarelated high signal intensity can appear in ligaments some time after an acute injury due to repair processes of scarring and fibrosis or fat replacement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17,19 However, these findings have been contradicted by several investigators who found no direct correlation to trauma or clinical symptoms. 2,21,24,25,29,30 Instead, as an alternative explanation, degeneration has been put forward as the source of these high signal changes. 37 This hypothesis was put to the test.…”
mentioning
confidence: 99%
“…4,8,9,13,22,28 Substantial variability in the morphology of the upper cervical ligaments has been shown in various studies using MRI. 16,20,24,29,32,35 Dark signals on proton-density (PD)-weighted images of the ALs are generally considered the norm. 19 However, high signal alterations of the ALs have frequently been reported in patients with (chronic) whiplash-associated disorder (WAD), 1,5,11,26,28,31 and also in uninjured individuals.…”
mentioning
confidence: 99%